Spectra of Ionized Atoms: From Laboratory to Space - Joseph Reader (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
The spectra of ionized atoms continue to play an important role in understanding a wide variety of plasmas. The relatively new discipline of Laser-Induced Breakdown Spectroscopy (LIBS) is being used on earth to produce lower ionization stages of atoms for diagnostics of samples, but also in space to determine contents of rocks on Mars and Venus. Spectra of lower stages of ionization are also found in nebulae, interstellar clouds, chemically peculiar stars, and in the sun. For higher ionization stages, there is continuing need for spectra found in the hot plasmas of tokamaks and other machines aimed at developing new energy sources. Since much of the data for these hot plasmas must come from ab initio calculations, laboratory experiments can serve to evaluate the accuracy of the calculations. Experiments with electron beam ion traps (EBITs) can remove all but a few remaining electrons and thus form a basis for evaluating calculations of ions having only a few electrons. This Special Issue of Atoms highlights the need for continuing research on the spectra of all types of ionized atoms.